(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article examines in detail the pathophysiological mechanisms of bone marrow microenvironment transformation in chronic lymphocytic leukemia (CLL). The concept of "niche dependency" of tumor cells is substantiated. Changes in mesenchymal stem cells, the vascular component, and the immune landscape of the niche are analyzed. The role of exosomal transport and hypoxia in the development of drug resistance is considered.